XALQ HUNARMANDCHILIGINI O’RGANISHNING O’ZIGA XOS XUSUSIYATLARI (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
In this article, the knowledge to be acquired in the study of various fields of folk crafts, the history, origin, ethnic roots of certain professions, folk craftsmen and their creative activities; issues such as the form and role of handicrafts in world culture, distribution of branches, geography, types, and their directions were discussed